Organophosphorus Insecticide Poisoning (EJIFCC, 1999)
Organophosphorus insecticide poisoning is a major global health problem with approximately 3 million poisonings and 200,000 deaths annually. These irreversible inhibitors of acetylcholinesterase produce a well established triphasic effect in man. The initial cholinergic phase due to accumulation of acetylcholine at muscarinic, nicotinic, and central nervous system synapses is a medical emergency that often requires treatment in an intensive care unit. The intermediate syndrome sets in 2-4 days after initial exposure, due to pre-and postsynaptic dysfunction at the neuromuscular junction, and causes respiratory failure for which ventilatory care is necessary. The delayed polyneuropathy sets in about 21 days after exposure, due to phosphorylation of neuropathy target esterase, and produces symmetrical motor weakness of peripheral muscles with a variable sensory component. The organophosphorus compounds are known to produce effects on the nervous, cardiovascular, and reproductive systems in man and animals, producing a wide range of effects. Further interference with temperature regulation, metabolic and endocrine function along with disturbances in vision, affection of vocal cords, and immunity could present challenging medical scenarios for a clinician. Biochemical assays of cholinesterase and organophosphorus agents have undergone considerable review, and progress is being made to develop scientifically reliable criteria for diagnosis and management. Atropine and pralidoximes have been the major therapeutic agents for intoxication, but the unacceptable mortality and morbidity associated with poisoning necessitates change and the use of agents like clonidine and fluoride, which have potentially beneficial effects. There is need for collaborative research and study between the technologically developed countries and the third-world countries, where the vast majority of health disorders associated with organophosphorus insecticides is encountered.